Colliding EM Waves that Admit Separable Wave Equation - Halilsoy, Mustafa (General Relativity and Gravitation, Springer, 1994)
We show that the massive wave equation is separable in two particular colliding Einstein-Maxwell waves space-times. The first is the type D metric of Chandrasekhar and Xanthopoulos whereas the second is the doubly polarized Bell-Szekeres solution which is of Petrov type General.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/BF02105154) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Bell-Szekeres; Xanthopoulos; Einstein-Maxwell; gravity; Petrov type General